Política e educação de 1930-1961 : a concepção de público no manifesto dos educadores de 1959 - Pasinato, Darciel (2014)
The Educators Manifesto of 1959 was an important and innovative because it put into debate key issues in Brazilian society, especially education, understood as the right of all. Moreover, defended is conception of public school, compulsory, free and secular. Thus, the research problem seeks to answer, as the signatories of the Manifesto understand the concept of audience and how to do it from a critique of existing education and advocates of private school education in solving historical problems of Brazil. In these propositions, clashed with supporters of private schools, especially with regard to the issue of public funding. The overall goal of the research is to analyze educational problems in Brazil, in the context of the 1930s and 1960s, as well as the solutions proposed in the Manifesto of 1959. Research is likely bibliographic and documentary. The bibliographic part includes books, chapters and journal articles that deal with social, economic, political and educational issues surrounding context. The documentary section includes both manifest and a collection of articles published in magazines and Voices Anhembi, which express the two main currents faced: Liberals and Catholics. The paper analyzes the consequences and impacts of the 1930 Revolution in the consolidation process of the state institution as formulator of social and educational policies, especially in relation to education. Also addresses, discussions and placements of Liberals and Catholics served in the two magazines mentioned and basic aspects of the campaign in defense of public schools, as well as innovations in the Manifesto of 1959 in relation to the Manifesto of 1932. In summary, it comes up, to examine the clashes between those who supported the public school and private school advocates, served by two major magazines. The studies allow us to state that the understanding of this Manifesto in 1959 , the public does not restrict only to the idea of public funding; signatories argued that the money from the Federal Government should be designed only to public school; and that private schools should be audited by the state and finally, through the Manifesto 1959, showed solutions for improving Brazilian education period, charging that the state should assume their role in the provision of quality education and also in ensuring the permanence of students in public school